2021
DOI: 10.3390/biomedicines9080962
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Sidedness, RAS and BRAF Mutations and MSI Status as Prognostic Factors in Patients with Colorectal Liver Metastases Treated with Surgery and Thermal Ablation: Results from the Amsterdam Colorectal Liver Met Registry (AmCORE)

Abstract: The aim of this study was to assess primary tumor sidedness of colorectal cancer (CRC), rat sarcoma viral oncogene homolog (RAS) and v-raf murine sarcoma viral oncogene homolog B (BRAF) mutations and microsatellite instability (MSI) status as prognostic factors predicting complications, survival outcomes, and local tumor progression (LTP) following surgery and thermal ablation in patients with colorectal liver metastases (CRLM). This Amsterdam Colorectal Liver Met Registry (AmCORE) based study included 520 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
0
18
1
1
Order By: Relevance
“…Even if all these studies included patients with tumors larger than 3 cm, which is questionable, in multivariate analysis, the 2 main risk factors of local tumor progression were mutational status and ablation margins (Tables 2 and 3). These data were also confirmed by a more recent study from the Amsterdam group [60]. The authors analyzed the impact of primary tumor sidedness, genetic mutations (RAS and BRAF) and the microsatellite instability status to determine the prognosis of patients treated for CRLM enrolled in the Amsterdam Colorectal Liver Met Registry.…”
Section: Implication Of Ras Mutations In Ablative Treatment Of Crlmmentioning
confidence: 71%
See 1 more Smart Citation
“…Even if all these studies included patients with tumors larger than 3 cm, which is questionable, in multivariate analysis, the 2 main risk factors of local tumor progression were mutational status and ablation margins (Tables 2 and 3). These data were also confirmed by a more recent study from the Amsterdam group [60]. The authors analyzed the impact of primary tumor sidedness, genetic mutations (RAS and BRAF) and the microsatellite instability status to determine the prognosis of patients treated for CRLM enrolled in the Amsterdam Colorectal Liver Met Registry.…”
Section: Implication Of Ras Mutations In Ablative Treatment Of Crlmmentioning
confidence: 71%
“…In these studies, the optimal minimal ablation margin was >5 mm [56,58] and raised to 10 mm [57,59]. Wider margins seem to be necessary to reduce rates of local tumor progression in RAS/KRAS mutation patients [60].…”
Section: Implication Of Ras Mutations In Ablative Treatment Of Crlmmentioning
confidence: 94%
“…Regarding microsatellite instability (MSI), a screening study of deficient mismatch repair profiles on colorectal cancer distribution in Romania by Lungulescu showed that MSI status does not carry a significant prognostic role [ 70 ]. Apart from clinical and pathological factors, new insights regarding the role of genetic [ 71 ], transcriptomic [ 72 ] and mass spectrometry imaging proteomics analysis [ 73 ] as prognostic instruments are still under investigation concerning the influence upon clinical decision in loco-regional recurrence prediction. Additionally, immunohistochemical expression of the REG4 proteins, frequently detected in right colon cancer, was significantly correlated with low recurrence-free survival [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…After accounting for potential confounders in multivariable analysis using Cox proportional hazards model and performing subgroup analyses to identify heterogeneous treatment effects, the risk of confounding should be minimized and the risk of residual confounding is limited. However, the MSI and RAS and BRAF mutation status were not routinely established and could be potential confounders leading to residual bias, as RAS mutations status might influence LTPFS [ 12 , 43 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. The selection of patients for NAC was based on local expertise, determined by multidisciplinary tumor board evaluations, and not preceded by protocol, which may have driven treatment decisions and could preserve selection bias and might impair the generalizability of the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic therapy increased 5-year overall survival (OS) of unresectable CRLM from 0–3% for untreated CRLM to 11% for patients treated with palliative chemotherapy [ 5 , 6 , 7 , 8 , 9 ]. Local treatment with curative intent improves 5-year OS up to 58% for resectable and/or ablatable CRLM [ 10 , 11 , 12 , 13 , 14 , 15 ]. Unfortunately, roughly 20% of patients with CRLM are eligible for local treatment options, such as partial hepatectomy or thermal ablation (i.e., radiofrequency ablation (RFA), microwave ablation (MWA)) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%